Legal Protection and Liability of Anesthesiologists in High-Risk Medical Procedures: A Normative Juridical Study - Dewi Puspitorini Husodo; Francis Maryane Pattynama; Ahmad Heru Romadhon (Smart Society, 2026)
Medical complications in anesthesiology frequently create legal disputes due to the unclear distinction between inherent medical risks and medical negligence in Indonesian healthcare practice. Previous studies generally discuss medical malpractice broadly, while limited research specifically examines legal protection and proportional liability for anesthesiologists in high-risk medical procedures. This study aims to analyze the forms of legal protection for anesthesiologists and determine the limits of their legal liability within the Indonesian healthcare legal system. This research uses a normative juridical method with statutory, conceptual, and case approaches. Primary legal materials include Law Number 17 of 2023 on Health, the Civil Code, and the Criminal Code, supported by legal doctrines and scholarly literature. The analysis applies qualitative legal reasoning through systematic interpretation and doctrinal analysis. The findings show that legal protection for anesthesiologists consists of preventive and repressive mechanisms. Preventive protection is implemented through professional standards, standard operating procedures, informed consent, medical records, and patient safety systems. Repressive protection is conducted through mediation, medical audits, disciplinary proceedings, and litigation as a last resort in resolving medical disputes. The study also finds that legal liability in anesthesiology only arises when unlawful conduct, fault, damage, and causality are cumulatively proven. The novelty of this study lies in positioning anesthetic complications as inherent medical risks rather than automatically categorizing them as malpractice. The research contributes to the development of proportional medical liability theory and strengthens a standard-based approach in Indonesian health law.